Peranan Pajak Daerah dan Retribusi Daerah Terhadap Pendapatan Asli Daerah (PAD) di Kabupaten Lombok Barat - Muhamad Sayuti (Universitas Hamzanwadi, 2020)
This study aims to determine the role of local taxes and levies on local revenue (PAD) in West Lombok Regency. This type of research is descriptive with a caulitative approach. The unit of observation is the regional taxes and levies of West Lombok Regency. Analysis and interpretation of data by means of data reduction, data verification, data presentation, and drawing conclusions. The results show that in general the effectiveness of West Lombok Regency in collecting local taxes and levies to increase local revenue (PAD) for the last five years is quite effective where in 2015-2019 the highest regional taxes occurred in 2016 with a percentage of 88.89% , while the highest regional retribution occurred in 2015 with a percentage of 100.43%. Local taxes and levies in West Lombok Regency are very important because they are used to build facilities and infrastructure for the benefit of the community, for example the construction of hospitals, other forms of community service, besides physical development / locality, business development, employment opportunities and community economic development.